Easy and fast obtaining of magnetic graphite - Nunes, Franciane Batista; Salles, Theodoro da Rosa; Vincensi, Enzo Cassol; Vargas, Guilherme Oliveira; Vidal, Leonardo Zancanaro; Pimentel, Amanda Carolina; Bruckmann, Franciele da Silva; Bohn Rhoden, Cristiano Rodrigo (Disciplinarum Scientia | Naturais e Tecnológicas, 2021)
The exceptional properties of graphite, such as excellent thermal and electrical conductivity, corrosion resistance, allow this material to be widely explored in the industrial sector as an anatomic component in different material applications for instance lithium batteries. Magnetic nanoparticles, such as magnetite, presented biocompatibility, biodegradability, thermal conductivity, chemical stability, and the possibility of formation of nanocomposites. Thus, this work proposed the magnetization of graphite through a co-precipitation method that employs FeCl2 as an iron source. This methodology proved a magnetics nanocomposite with different amounts of magnetite incorporated and control of that. The results obtained through the instrumental analysis of XRD demonstrate a high crystallinity of the material and the presence of magnetite on the surface of the graphite. The average crystallite size, updated by the Scherrer equation, shows a decrease of the size as more nanoparticles are incorporated into the nanomaterial. Finally, it is possible to confirm the obtainment of a magnetic nanocomposite using a fast, economical and efficient method.